Modeling of Electrokinetic Remediation Combining Local Chemical Equilibrium and Chemical Reaction Kinetics - Masi, Matteo; Paz-García, Juan Manuel; Gómez-Lahoz, César; Villén-Guzmán, María Dolores; Ceccarini, Alessio; Iannelli, Renato (My University, 2020)
A mathematical model for reactive-transport processes in porous media is presented. The modeled system includes diffusion, electromigration and electroosmosis as the most relevant transport mechanism and water electrolysis at the electrodes, aqueous species complexation, precipitation and dissolution as the chemical reactions taken place during the treatment time. The model is based on the local chemical equilibrium for most of the reversible chemical reactions occurring in the process. As a novel enhancement of previous models, the local chemical equilibrium reactive-transport model is combined with the solution of the transient equations for the kinetics of those chemical reactions that have representative rates in the same order than the transport mechanisms. The model is validated by comparison of simulation and experimental results for an acid- enhanced electrokinetic treatment of a real Pb-contaminated calcareous soil. The kinetics of the main pH buffering process, the calcite dissolution, was defined by a simplified empirical kinetic law. Results show that the evaluation of kinetic rate entails a significant improvement of the model prediction capability.
Keywords: Cinética química; Reactive-transport model; Calcite dissolution kinetics; Electrokinetic remediation; Local chemical equilibrium